2004
DOI: 10.1007/978-3-540-24612-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Mediated Distributed Knowledge Management

Abstract: Distributed Knowledge Management is an approach to knowledge management based on the principle that the multiplicity (and heterogeneity) of perspectives within complex organizations is not be viewed as an obstacle to knowledge exploitation, but rather as an opportunity that can foster innovation and creativity. Despite a wide agreement on this principle, most current KM systems are based on the idea that all perspectival aspects of knowledge should be eliminated in favor of an objective and general representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…This may lead to more satisfaction to end users, who are already familiar with the interface and methods applied in the systems in use. These aspects are compliant with the Distributed Knowledge Management approach [1] which prescribes that more attention should be given the knowledge holders and the natural processes they already use to share knowledge within organizations, which leads to a bottom-up strategy when proposing a KM solution.…”
Section: Agent Organizations As Metaphors In Km Modelingmentioning
confidence: 95%
See 1 more Smart Citation
“…This may lead to more satisfaction to end users, who are already familiar with the interface and methods applied in the systems in use. These aspects are compliant with the Distributed Knowledge Management approach [1] which prescribes that more attention should be given the knowledge holders and the natural processes they already use to share knowledge within organizations, which leads to a bottom-up strategy when proposing a KM solution.…”
Section: Agent Organizations As Metaphors In Km Modelingmentioning
confidence: 95%
“…Moving on with the analysis, Figure 3 shows basic goal dependencies between the scenario's actors. 1 The reason for modeling team working well as a softgoal refers to the fact that the organization is not monitoring and measuring explicitly the team work quality. In the process of analyzing goals from the point of view of the organization, positive and negative contributions of the team working well softgoal to the other goals of the organization will be modeled explicitly.…”
Section: Strategic Dependenciesmentioning
confidence: 99%
“…Therefore, working based on traditional, centralized knowledge management systems becomes infeasible. While there are some technical solutions toward Peer-to-Peer knowledge management systems (e.g., [3]) -and we have developed a technically sophisticated solution of our own as part of our project, SWAP -Semantic Web and Peer-to-Peer [4], traditional methodologies for creating and maintaining knowledge structures appear to become unusable like the systems they had been developed for in the first place.…”
Section: Introductionmentioning
confidence: 99%
“…Outside of the Semantic Web, [6,7] proposes a distributed knowledge management infrastructure based on Kpeers. An interesting point of this solution is that knowledge is created and shared using a bottom-up approach.…”
Section: Machine Processable Semantics Organizational Modelmentioning
confidence: 99%
“…Instead of centralized systems that forces users to agree in a set of rules, schemas and data, CSpaces offer a distributed infrastructure where users can publish personal knowledge that can be shared with other users with common information/interests. This approach is inspired in an earlier proposal called Distributed Knowledge Management [6,7] where its authors confirmed during the realization of several tests in real scenarios that users were more favorable to this kind of approach because it takes into account the different perspectives and understandings that users have about the world and more concretely about the information, processes and interactions of their organizations or working groups. The combination of Individual CSpaces can generate a new space shared by all these users.…”
Section: Personal and Distributed Knowledge Managementmentioning
confidence: 99%